Dynamics of changes in bacteriological and morphometric parameters at decreasing colonization resistance of bird intestine - Ekaterina M. Lenchenko; Vladislav V. Ponomarev (RUDN Journal of Agronomy and Animal Industries, 2025)
Decrease in compensatory mechanisms of natural resistance due to changes in composition of evolutionarily formed microbiocenoses, increases risks of developing a syndrome of excessive growth of antibiotic-resistant microorganisms. The aim of the study was to analyze the dynamics of changes in bacteriological and morphofunctional parameters with a decrease in colonization resistance of the intestine of birds. To assess quantitative and species composition of microorganisms, the colonization index of bacteria isolated from the caecum contents of intestine of clinically healthy and sick birds was considered. The dynamics of changes in morphofunctional parameters during the dissemination of pathogenic bacteria into tissues and organs was studied using cytological and histochemical data. The number of microorganisms isolated from the caecum contents of intestine of sick birds significantly increased, the colonization index of lactose-positive bacteria was 0.2470.283; lactose-negative bacteria - 0.6570.730. With excessive bacterial contamination of ileocecal part of intestine and translocation of pathogens outside gastrointestinal tract, signs of dystrophy, necrosis and rejection of epithelial cells of mucous membrane of respiratory and digestive systems developed. The initiation, development and outcome of the infectious process are mediated by stability of homeostasis of susceptible macroorganisms and realization of pathogenic potential of isolates producing adhesive antigens, bacteriocins, hemolysins, and cytotoxins.